Analisa Sistem Kerja Kondensor terhadap Nilai Set Point Chiller Trane Tipe CVHG0780 - Arnas, Yenni; Mediaswati, Cristina Novi; Izaty, Hadina Shofia; Wahyu, Anggy; Krisdian, Safa; Marpaung, Ray Ivan (Jurnal Teknik Mekanikal Bandar Udara, 2023)
The chiller is one of the devices in the air conditioning system that functions as a heat exchange device. At the airport, the chiller serves as a heat exchange device that will be distributed to the terminal area. The chiller that's on must have a cost for the operation and maintenance of the chiller. Therefore, it is veryimportant to have a condenser working system analysis against the set point chiller value in this study using a Trane brand chiller with type CVHG0780. This set point affects the chiller condenser's operating system. Hopefully this journal will provide a clarification of set point settings for chiller use. To find the best set point, this study collected data by conducting experiments on each chiller operating, then collected the data, and finally processed the data to find the set point that can be justified in the operation of the chiller brand Trane with type CVHG0780, which is the target in this study.